Using GIS methods in environmental modelling the Bihar Plain - Tomor, Tamás; Tamás, János; Bíró, Tibor (Acta Agraria Kaposváriensis, 2002)
The law to use GIS tools in the process of decision making in regional development defines it, but its integration level and analysing method is not cleared yet. We would like to introduce a GIS research project in which we want to work out a data collection – preparation – analysis method in order to support the decision makers in this sector. Our system collect, prepare and integrate a big amount of high scale map data in itself for a geographically well impounded area, the Bihar plain. The data represent the environmental elements and the analysis will show us the potential danger of the environmental conflicts. The aim of the research is to develop a model on a regional scale, which can support an up to date information technological method and can be connected to the relevant rural development methodologies. As a methodological part of this the aim is to work out such an integrated geographical information system which proves that during a detailed environmental impact assessment it is possible to combine the methodology of the geographical information system with risk-assessment on the potential danger of environmental damages.